2021
DOI: 10.1016/j.jsps.2021.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Cold-pressed raspberry seeds oil ameliorates high-fat diet triggered non-alcoholic fatty liver disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is considered one of the most serious public health problems affecting liver. The reported beneficial impact of raspberries on obesity and associated metabolic disorder makes it a suitable candidate against NAFLD. In the current study, the chemical profile of raspberry seed oil (RO) was characterized by analysis of fatty acid and tocopherol contents using high-performance liquid chromatography (HPLC) in addition to the determination of total phenolic and flavonoids. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…No less important, the antioxidant determined in plant tissues as well as in animals is vitamin E (tocopherols), for which the antioxidant activity is concentration-dependent [ 43 ]. According to Hendawy et al’s [ 44 ] research data, the total tocopherol content in cold-pressed raspberry seeds’ oil is 185.1 mg 100 g −1 oil. Mildner-Szkudlarz et al [ 45 ] provided data that raspberry seeds contain about 235.37 mg 100 g −1 oil of total tocopherols, while according to Li et al [ 46 ], in blackberry seeds the total tocopherols are 28.63 mg 100 g −1 oil.…”
Section: Resultsmentioning
confidence: 99%
“…No less important, the antioxidant determined in plant tissues as well as in animals is vitamin E (tocopherols), for which the antioxidant activity is concentration-dependent [ 43 ]. According to Hendawy et al’s [ 44 ] research data, the total tocopherol content in cold-pressed raspberry seeds’ oil is 185.1 mg 100 g −1 oil. Mildner-Szkudlarz et al [ 45 ] provided data that raspberry seeds contain about 235.37 mg 100 g −1 oil of total tocopherols, while according to Li et al [ 46 ], in blackberry seeds the total tocopherols are 28.63 mg 100 g −1 oil.…”
Section: Resultsmentioning
confidence: 99%
“…Improving ALA metabolism and increasing serum ALA levels help treat metabolism-related diseases. Raspberry seed oil (RO) with a high level of ALA (25.98%) could effectively treat the HFFD-induced NAFLD mice (Hendawy et al, 2021). Han et al found that the intervention of ALA could activate the AMPK signaling and further improve mitochondrial dysfunction and oxidative stress, treating NAFLD mice induced by HFFD (Han et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Hendawy et al studied the effect of cold-pressed raspberry seed oil on non-alcoholic fatty liver disease (NAFLD) in male Wistar rats [ 47 ]. NAFLD is a pathologic condition of the liver characterized by excessive deposition of fat in hepatocytes.…”
Section: Health-promoting Properties Of Berry Seeds—in Vitro and In V...mentioning
confidence: 99%
“…It is correlated with type II diabetes, obesity, insulin resistance, elevated serum lipoproteins, and hypertension, and can lead to permanent liver damage. As NAFLD is a problem that affects 7–37% of adults and 20–30% of children worldwide, and currently used drugs (anti-obesity, antidiabetic, antioxidant, and antihyperlipidemic) can cause adverse effects, researchers are still searching for new ways of prevention and treatment of this disease [ 47 , 48 ]. Raspberry oil has a good ratio of n -6 and n -3 fatty acids (2–3:1) and contains γ-tocopherol, linolenic acid, polyphenols, and carotenoids, so it was chosen as a potential candidate [ 6 , 47 , 49 ].…”
Section: Health-promoting Properties Of Berry Seeds—in Vitro and In V...mentioning
confidence: 99%
See 1 more Smart Citation